Data Rights Law 1.0 : the theoretical basis - Lian, Yuming (Peter Lang International Academic Publishers, 2019)
Since its emergence, big data has brought us new forms of energy, technology and means of organization which will generate greater values by crossover, integration, openness and sharing of data. Nevertheless, risks caused by open access and the flow of data also bring us enormous challenges to privacy, business secrets and social and national securities. This raises people?s awareness on data sharing, privacy protection and social justice, and becomes a significant governance problem in the world. In order to solve these problems, Data Rights Law 1.0 is innovative in that it proposes a new concept of the ±data person?. It defines ±data rights? as the rights derived from the ±data person? and ±data rights system? as the order based on ±data rights?. ±Data rights law? is the legal normative formed out of the ±data rights system?. In this way, the book constructs a legal framework of ±data rights-data rights system-data rights law?. If data is considered as basic rights, on which new order and laws are to be built, it will bring brand new and profound meaning to future human life.